Peningkatan Literasi Keuangan pada UMKM melalui Pelatihan dan Pendampingan Pembukuan Sederhana - Natasia Alinsari (Universitas Kristen Satya Wacana Salatiga, 2020)
UMKM are expected to be at the forefront of strengthening the economic pillars in achieving the Sustainable Development Goals (SGDs). This is because UMKM are one of the businesses that are most able to survive in a deteriorating economic condition, especially in the conditions of the Covid-19 pandemic. Therefore, UMKM must have good financial management so that the business can be sustainable. One of them is by having correct financial records and being able to compile the financial reports needed to make decisions in planning the next business strategy. UMKM Batik in Tegalrejo Village, Gedangsari, does not have good records so they are unable to produce financial reports. The results of training and assistance in making simple bookkeeping and compiling financial reports increase the awareness of UMKM of the importance of information generated by financial reports as a basis for decision making and formulating business strategies to achieve sustainable business.